Nutritional Composition of Seeds of False Mopane (Guibourtia coleosperma) from Shakawe and Kasane Areas, Northern Botswana - Olebogeng Matlhodi; Eyassu Seifu; Demel Teketay; Bonno Sekwati-Monang (International Journal on Food, Agriculture and Natural Resources, 2023)
The seeds of Guibourtia coleosperma serve as potential source of nutritious food for rural communities in northern Botswana though underutilized. The objective of this study was to determine the proximate and mineral composition of G. coleosperma seeds collected from northern Botswana. Seed samples were collected from Shakawe and Kasane areas in northern Botswana. The proximate composition and mineral contents of the seed were determined following standard procedures. The data were analyzed using T-test. Seeds collected from Shakawe had average moisture (%), crude fat (%), crude fiber (%), crude protein (%), ash (%), total carbohydrate (%) and energy (kcal/100g) contents of 8.48 ± 0.29, 9.24 ± 0.31, 4.72 ± 0.60, 15.34 ± 0.48, 2.40 ± 0.02, 59.81 ± 1.00 and 383.80 ± 4.81, respectively. The corresponding values for seeds collected from Kasane were 9.00 ± 0.10, 10.17 ± 0.37, 7.13 ± 0.21, 16.44 ± 0.43, 2.45 ± 0.02, 54.80 ± 0.58 and 376.50 ± 2.22, respectively. Seeds collected from Kasane had significantly higher (p< 0.05) crude fat, crude fiber, crude protein and ash contents than seeds collected from Shakawe. However, the total carbohydrates content of seeds collected from Shakawe was significantly higher (p< 0.05) than those collected from Kasane. No significant differences (p> 0.05) were observed for moisture and energy contents between the seed samples collected from the two locations. The predominate proximate component in the seeds was total carbohydrate followed by crude protein and, therefore, the seeds can serve as good sources of energy and protein. The average zinc, iron, magnesium, potassium, calcium, sodium (mg/100 g) and phosphorus (mg/g) contents of seeds collected from Shakawe were 2.96 ± 0.53, 2.40 ± 0.27, 116.80 ± 2.82, 468.69 ± 19.28, 316.70 ± 21.15, 1.21 ± 0.67 and 1.35 ± 0.04, respectively. The corresponding values for False Mopane seeds collected from Kasane were 2.53 ± 0.31, 3.34 ± 0.18, 173.65 ± 5.83, 460.86 ± 10.53, 367.59 ± 15.37, 3.51 ± 0.44 and 1.45 ± 0.12, respectively. The values for iron, magnesium, calcium and sodium were significantly higher (p< 0.05) for seeds collected from Kasane than those collected from Shakawe. However, no significant differences (p> 0.05) were observed between the seed samples collected from the two locations for zinc, potassium and phosphorus. Quantitatively, the predominant mineral observed in seed was potassium followed by calcium. The seeds could serve as good source of magnesium, iron, zinc, calcium and potassium since they contribute higher proportions of the recommended daily intake of these minerals. The results showed that location has a significant effect both on the proximate composition and mineral contents of False Mopane seeds.